A spatial analysis of dietary patterns in a large representative population in the north of The Netherlands – the Lifelines cohort study - Louise H. Dekker; Richard H. Rijnks; Dirk Strijker; Gerjan J. Navis (International Journal of Behavioral Nutrition and Physical Activity, 2017)
Abstract Background Diet is an important modifiable risk factor for chronic diseases. In the search for effective strategies to improve dietary patterns in order to promote healthy ageing, new approaches considering contextual factors in public health medicine are warranted. The aim of this study is to examine the spatial clustering of dietary patterns in a large representative sample of adults. Methods Dietary patterns were defined on the basis of a 111 item Food Frequency Questionnaire among n = 117,570 adults using principal components analysis. We quantified the spatial clustering of dietary pattern scores at the neighborhood level using the Global Moran’s I spatial statistic, taking into consideration individual demographic and (neighborhood) socioeconomic indicators. Results Four dietary patterns explaining 27% of the variance in dietary data were extracted in this population and named the “bread and cookies” pattern, the “snack” pattern, the “meat and alcohol” pattern and the “vegetable, fruit and fish” pattern. Significant spatial clustering of high (hot spot) and low (cold spot) dietary pattern scores was found for all four dietary patterns irrespective of age and gender differences. Educational attainment and neighborhood income explained the global clustering to some extent, although clustering at smaller regional scales persisted. Conclusion The significant region-specific hot and cold spots of the four dietary patterns illustrate the existence of regional “food cultures” and underscore the need for interventions targeted at the sub-national level in order to tackle unhealthy dietary behavior and to stimulate people to make healthy dietary choices.